Innovation pédagogique à l’université et effets de transformation sur les enseignants - Loïse Jeannin; Guillaume Serres; Carine Roblès; Ariane Tichit; Laurence Hamon (Recherches en Éducation)
We study faculty members’ experience of managing a pedagogical innovation project at university to better understand their experience and their possible feeling of transformation. Twenty-one lecturers, managing a pedagogical innovation project during the 2018-2020 period in a French university, answered a questionnaire. Results, based on a mixed approach (thematic analysis and occurrences’ counting), showed motivational drivers revolving around students’ needs, professional recognition or self-realization. Faculty members described positive and negative factors impacting the project’s success, along with a mixed feeling of transformation. If many lecturers perceive a change in their pedagogical practices, they do not all consider having been transformed by the project.